SUBVERSIVE COMMEMORATION: MAPPING THE ASSEMBLAGE OF COUNTER-MEMORY ON TWITTER - Gaw, Fatima; Bunquin, Jon Benedik (AoIR Selected Papers of Internet Research, 2021)
Beyond enabling participatory forms of memory-making, digital media reconfigure power relations in memory construction. In the Philippines, we witness this through the hashtag network #ArawNgMagnakakaw (‘Day of Thieves’) to counter the heroic commemoration of the dictator Ferdinand Marcos sanctioned by the state and supported by online networks that distort and deny his crimes during his 20-year regime. This case illustrates not only how digital media facilitates the negotiation of memory by non-institutional actors, but also how it sets the conditions to resist elite narratives through non-conventional ways of remembering. This study examines the performance of counter-memory (Foucault, 1977) in the intersection of networked publics, counter-narratives, and technologies of memories. We investigate the hashtag network #ArawNgMagnanakaw by mapping its social network and analyzing its discourses as digital practices (Jones, Chik & Hafner, 2015). We argue that the network derives its power from neither elite nor collective actions, but through connective action of structures, discourses and practices of remembrance. Firstly, the locus of analysis shifts from a single actor (‘who remembers’) to the assemblage (‘what enacts the remembering’) as an agent of counter-memory, with technology shaping its possibilities and boundaries. Secondly, the assemblage’s resistance to elite commemoration surfaces silenced and neglected historical narratives (‘what is remembered’) through affective articulations of protest and subversive commemorative practices (‘how is it remembered’). We theorize the ‘assemblage of counter-memory’ as the connective, discursive, and material assemblage that enact political agency to privilege marginalized narratives and play an active role in the (re)construction of memory.